Making the Psalter One’s "Own Language": Jonathan Edwards Engages the Psalms - Barshinger, David P. (Jonathan Edwards studies, 2012)
While Jonathan Edwards is hailed as a great theologian and philosopher, few remember him for his exegesis of Scripture. Yet every day Edwards delved into the Bible, searching for a deeper understanding of God and divine things; indeed, the Scriptures saturate Edwards’ sermons, treatises, and several notebooks he kept for personal study. In this essay, I seek to demonstrate the significance of the Psalms, one of Edwards’ favorite books of the Bible, in his life, biblical interpretation, worship, and preaching. Also, by outlining seven major theological themes that Edwards developed in his engagement with the book of Psalms—God’s glory, human depravity, Christ’s broad work, the heralding of the gospel by the Spirit, the church, the call to vital piety, and the eschatological judgment and hope—I argue against labeling Edwards’ exegesis of the Psalms as merely "Christological," claiming that such a description is too narrow for the variety of ways in which he engaged the Psalter. Instead, I suggest that Edwards’ interpretation of the Psalms was "redemptive-historical"—governed by the Trinity’s work of redemption in history